Antitumor Activity Of Aloe Vera Against Ehrlich Ascitis Carcinoma (EAC) In Swiss Albino Mice - NAVEENA,; BHARATH B K,; SELVASUBRAMANIAN, (International Journal of Pharma and Bio Sciences, 2011)
Antitumor activity of 50% ethanol extract (100 mg/kg) of Aloe vera was evaluated against Ehrlich ascites carcinoma (EAC) tumor in mice. After 24 h of tumor inoculation, the extract was administered daily for 14 days. After administration of the last dose followed by 18 h fasting, mice were sacrificed for observation of antitumor activity. The effect of Aloe vera on the growth of transplantable ascites tumor, body weight of EAC bearing hosts and simultaneous alterations in the hematological profile, serum (ALT, AST, LDH, ALP and glucose) and liver biochemical parameters (lipid peroxidation, GSH and antioxidant enzymes) were estimated. The Aloe vera showed decrease in abdominal circumference and body weight of EAC tumor bearing mice. Hematological profile reverted towards normal levels in extract treated mice. Treatment with Aloe vera restored the serum biochemical parameters towards normal levels and decreased the levels of lipid peroxidation and increased the levels of reduced glutathione and other antioxidant enzymes (SOD, CAT and GPx). The 50% ethanol extract of Aloe vera exhibited antitumor effect by modulating lipid peroxidation and augmenting antioxidant defense system in EAC bearing mice.